Investigating the Influence of Hybrid and Independent Learning on Student Learning Outcomes in European History Courses - Hanif Harahap; Madhan Anis; Ramazan Ramazan; Tengku Muhammad Sahudra (AL-ISHLAH: Jurnal Pendidikan, 2024)
The importance of implementing a hybrid learning model that combines face-to-face teaching with online computer-assisted teaching to create an integrated learning approach and student learning independence. The purpose of this study was to analyze the effect of hybrid and independent learning on student learning outcomes in European History courses. This study adopts a quantitative method and a quasi-experimental design. In collecting data the researchers used multiple-choice test techniques and questionnaires to examine students’ learning independence. The data analysis technique used is the Two-way ANOVA statistical test. The results of the study showed that there was an increase in student history learning outcomes for European history courses with "moderate" criteria with a score of 0.54 (0.3 N-Gain ≤0.7) after the implementation of hybrid learning. Hybrid learning has an effect on student learning outcomes in history education with a sig model value of 0.002, where the value is less than 0.05 (0.002 0.05). Independent learning has an impact on student learning outcomes with a sig questionnaire value of 0.042 where the value is less than 0.05 (0.042 0.05). In conclusion, in European history courses offered the learning model and learning independence has an impact on students' learning outcomes.